Republic of Poland : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2015)
This Selected Issues paper employs a suite of models to determine the main drivers of inflation in Poland. Inflation in Poland has stayed below the lower bound of the target band for about two years with external shocks adding to downward pressure during 2014. The paper provides a range of inflation forecasts to assess the likelihood of protracted low inflation. The paper considers the main factors underlying recent inflation developments and assesses the importance of first-round indirect and second-round effects of external shocks for headline inflation. Using a variety of models, the paper also provides possible forecast paths for inflation in Poland.